L’esprit publicitaire - Roland Canu; Bastien Soutjis (Communication)
Analysis of a large corpus of literature on advertising produced by advertisers, as well as by sociologists and economists suggests that the desire for legitimacy inherent in advertisers’ activities reflects two parallel quests, each of which are addressed in separate sections of this article. On one hand there is the quest for effective advertising techniques and messages likely to convince sometimes skeptical economic partners. On the other hand, there is a quest for acceptability for these techniques and messages, acceptability that may help limit criticism from civil society.